Differential expression of genes implicated in liver lipid metabolism in broiler chickens differing in weight. Issue 1 (2nd January 2020) - Pirany, N.; Bakrani Balani, A.; Hassanpour, H.; Mehraban, H.
ABSTRACT: 1. Lipid parameters and expression of ACACA, APOA1, CPT1A, FASN, FOXO1, LIPG, PPARα and SIRT1 genes involved in lipid metabolism were investigated in two groups of high (HW) and low (LW) weight broilers from the same strain. 2. Blood cholesterol and liver triglyceride levels were significantly increased in HW chickens compared to LW broilers, while other parameters, i.e. blood triglyceride, blood HDL/LDL, liver cholesterol and total liver fat showed no significant changes in either group. 3. The relative expression of ACACA, APOA1 and CPT1A genes was significantly lower in the liver tissues of HW broilers than in the LW group. The mRNA levels of these three genes showed a significant negative correlation with abdominal fat deposition and live weight of broilers. However, relative expression of FASN, FOXO1, LIPG, PPARα and SIRT1 hepatic genes did not differ among broilers. 4. It was concluded that, of eight hepatic genes implicated in lipid metabolism, only the expression of three ( ACACA, APOA1 and CPT1A ) were significant for fat and leanness within the same strain of chicken. Since reducing body fat is a major goal in the broiler industry, these data can provide fresh insight into the molecular processes underlying the regulation of fat deposition in broilers.